Liensinine suppresses STAT3-dependent HK2 expression through elevating SHP-1 to induce apoptosis in hepatocellular carcinoma cells in vitro and in vivo. (June 2018) - Shu, Guangwen; Hao, Ji; Li, Wei; Zhang, Lang; Qiu, Yunhan; Yang, Xinzhou
Graphical abstract: Highlights: Liensinine induces apoptosis in hepatocellular carcinoma (HCC) cells. Liensinine exhibits undetectable toxic effects on tumor-bearing mice. Liensinine provokes HCC cell apoptosis via modulating the SHP-1/STAT3/HK2 cascade. Abstract: Liensinine is an alkaloid from the embryos of Nelumbo nucifera Gaertn. Here, we revealed that liensinine induces hepatocellular carcinoma (HCC) cell apoptosis. Accumulation of ROS participates in liensinine-induced apoptosis. Mechanically, liensinine inhibits the expression of hexokinase 2 (HK2) and metabolism of glucose through glycolysis. In addition, liensinine increases SHP-1 expression, impairs STAT3 transactivity, and declines the binding between STAT3 and HK2 promoter. Loss of function analysis revealed that upregulation of SHP-1 is a critical event mediating liensinine-induced inhibition of the STAT3/HK2 cascade. Moreover, knockdown of SHP-1 abrogates liensinine-provoked glycolysis inhibition, ROS generation, and subsequent cell apoptosis. Animal studies showed that liensinine induces transplanted H22 cell apoptosis in vivo with few toxic effects on the host. Consistent with the in vitro data, liensinine modulates the SHP-1/STAT3/HK2 axis in vivo . Our findings support considering liensinine as a novel functional food ingredient applied in clinical HCC treatment.